Microgrid Power System Modeling Using the Multi-Agent Systems Concept and Stabilization by Lyapunov-Based Cooperative Controller During Disturbance and Load Shedding - Mohammad Tolou Askari; Z. Zandi (AUT Journal of Electrical Engineering, 2022)
The microgrid power system has a nonlinear dynamic with many uncertainties, such as changes in wind power and solar irradiation. Sustaining such system requires a robust approach. In this paper, in order to deal with this problem, the properties and concepts of multi-agent systems are used to model the microgrid power system, as this system has seven agents all of which have a common point production-consumption power. Afterwards, the design and implementation of cooperative control of the microgrid agents output power are discussed. Due to the fact that in the multi-agent modeling structure, each agent is related only to its neighbor agent, the designed controller is of decentralized or distributed type. Among the advantages of this distributed structure is the ability to adapt immediately and be resistant to uncertainties in the system. In addition, the advantages of the Lyapunov function in the cooperative control structure have been used in order to overcome the disturbances and uncertainties in the structure of the microgrid, and to ensure the stability of the system. Ultimately, the control law designed for the seven-factor model in MATLAB software is simulated and compared with similar previous methods.